Penyusunan Buku Panduan Praktis Penggunaan AI yang Beretika dalam Kegiatan Akademik Mahasiswa: Compiling a Practical Guidebook for the Ethical Use of Generative AI in Student Academic Activities - Tantri Annisa Hanjani; Retta Farah Pramesti; Gilar Budi Pratama (ITScience (Information Technology and Science), 2025)
This study addresses students' lack of understanding regarding the ethics of using Generative AI (Gen AI) in academic activities. This guidebook serves as a response to the increasing integration of generative AI technology in education, which requires students to adopt AI technology and use it responsibly and ethically. This study uses the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, and Disseminate). The research stages include content and technical needs analysis, content design and guidebook framework, development and limited trials with eight student representatives, validation of the guidebook's feasibility by experts and users, and dissemination of the guidebook to the target audience. The results show that experts consider this practical guidebook appropriate, with a Likert scale score of 3.6 for content, visuals, and technical aspects. The evaluation results show that 91.7% of students agree that this guidebook provides comprehensive information on the ethical use of Gen AI, and 66% of students agree that this book provides clear guidance for academic activities. This practical guidebook successfully addresses students' lack of understanding regarding the ethical use of Gen AI in academic activities. The student-centered approach is relevant, applicable, and potentially integrated into courses such as digital literacy or academic methodology. Further extensive testing and continued content development are recommended to align with technological updates for further research and broader implementation.